2023
DOI: 10.3390/sports11040080
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscape in Upper Limb Sports Rehabilitation and Injury Prevention

Abstract: This editorial aims to feature authors who intend to submit their research to this Special Issue of Sports entitled “Clinical Advances in Upper Limb Sports Rehabilitation and Injury Prevention” in areas that need special consideration [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our study underscores the importance of controlled and guided physical training to mitigate these risks. Notably, participants in our research predominantly focused on upper body strengthening, neglecting core and lower limb conditioning, which are vital for proper alignment and stability during shooting sessions [ 45 , 46 ]. Proper alignment not only enhances performance but also reduces the risk of shoulder injuries [ 46 , 47 , 48 , 49 ], a commonly affected area in archery.…”
Section: Discussionmentioning
confidence: 99%
“…Our study underscores the importance of controlled and guided physical training to mitigate these risks. Notably, participants in our research predominantly focused on upper body strengthening, neglecting core and lower limb conditioning, which are vital for proper alignment and stability during shooting sessions [ 45 , 46 ]. Proper alignment not only enhances performance but also reduces the risk of shoulder injuries [ 46 , 47 , 48 , 49 ], a commonly affected area in archery.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognised that athletes who engage in overhead activities often execute quick and forceful throwing overhead movements while serving a ball. These actions typically occur in positions that push the limits of their range of motion, thereby elevating the likelihood of shoulder or other upper limb injuries [ 1 , 2 , 3 ]. Nevertheless, the increased physical demands placed at the shoulder and elbow in overhead athletes may also affect physical performance during play [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experts in the field assert that prevention is key in managing overhead athletes, including evaluating and monitoring upper limb health and performance [ 6 , 7 ]. Patient-reported outcome measures (PROMs) are highly encouraged in this clinical population for assessing functional performance [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has observed a 40% prevalence of shoulder pain related to overuse pathology [2]. Maintaining optimal shoulder and arm function is not only essential for peak athletic performance but also critical for injury prevention and career longevity [3]. Although guidelines have been established, a significant portion of arm injuries in overhead sports result from non-traumatic musculoskeletal issues caused by overuse [4].…”
Section: Introductionmentioning
confidence: 99%